The Influence Earning Management on Firm Value by Good Corporate Governance Indeks as moderating variable ( Empirical studies on non finance companies listed on stock exchanges in Indonesia 2009-2012 ) - Despiendra Ferro; Haryetti '; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the research is to examine the effect Earnings Management on firm value by Good Corporate Governance Indeks as moderatin variable in non finance that listed in Indonesian stock exchanges(BEI) 2009 until 2012.The purposive sampling method is used to determine our samplengs . From one hundred eighty firms, we got fourty six firms. To analysis the data we use multiple regression analysis. T-test, F-test, anddetermine koefisien (